Mediasi Sebagai Alternatif Penyelesaian Sengketa Antara Bank dan Nasabah - Perjaka Purba (Kyadiren, 2021)
The current study is aimed to investigate the process of resolving disputes between banks and customers based on the legal provisions of (Bank Rakyat Indonesia) BRI Bank especially in Biak Regency and to investigate the alternative mediation process during dispute resolution between banks and customers. The research methodology is the library and the field research method based on the implementation occurred at Biak’s BRI Bank. In addition to reviewing the various needed domains in the study, the researcher also conducted observations and direct interviews with informants. The results of the study indicate that the alternative resolution between customers and the bank is conducted through non-litigation as a very efficient and effective method. The non-litigation mediation is simpler and relatively cheaper. The mediator is neutral and does not side with the parties. In addition, It is applied by Biak’s BRI Bank during dispute resolution due to its easiness and economical cost. Customers are indeed helpless against the Bank and only surrender at the court. To protect customer rights, banking mediation is established to resolve disputes. Mediation as the settlement benefits the parties because it is efficient in a relatively short time.